Analysis of the Metaphors in the Song ‘All Too Well’ by Taylor Swift as a Tool for Storytelling - Ela Sofiarti Sofian; F. X. Sawardi (Faculty of Humanities, Universitas Jenderal Soedirman, 2022)
Language is used by humans to communicate and express their ideas as well as feelings, which can be done through literary works such as a song. A song conveys an idea and/or a feeling through its lyrics. In a song, the lyrics may contain various metaphors that carry contextual meaning in order to convey a feeling and emotion. Thus, people may have different interpretation of a song. This applies to all kinds of songs, such as the longer version of Taylor Swift's song,